Comprehensive study of three novel cases of TFEB‐amplified renal cell carcinoma and review of the literature: Evidence for a specific entity with poor outcome. Issue 3 (20th December 2017) - Mendel, Lionel; Ambrosetti, Damien; Bodokh, Yohan; Ngo‐Mai, Mélanie; Durand, Matthieu; Simbsler‐Michel, Cécile; Delhorbe, Mickael; Amiel, Jean; Pedeutour, Florence
Abstract: The first case of TFEB‐amplified renal cell carcinoma was published in 2014. Since then, 29 additional cases have been described. The prognostic and therapeutic implications of this rare entity remain to be determined. We describe here the clinical, histological, and genetic features of three novel cases, and the first complete literature review. Four tumors were examined from three patients selected from the large collection of genetically characterized renal tumors in our institution. The pathological and immunohistochemical features were centrally reviewed by a uropathologist. Quantitative and structural genomic abnormalities were analyzed using comparative genomic hybridization, fluorescence in situ hybridization, and next generation sequencing. The three cases showed high‐level amplification but no translocation of TFEB. Histologically, two tumors showed a papillary or pseudopapillary architecture. They did not show similarities with renal cell carcinoma harboring translocation of TFEB. The tumors were locally advanced high‐grade lesions. They exhibited a metastatic course, which was rapidly leading to death in one patient. A second patient developed metastatic disease that did not respond to four lines of targeted treatments. The third patient had a protracted history of pulmonary and cardiac metastases. Complete clinical and biological data were examined and compared to those of the reported cases. Within the classification of renal tumors, TFEB‐amplified renal cell carcinoma may constitute a novel entity characterized histologically by high‐grade, papillary or pseudopapillary architecture, and necrotic remodeling and clinically by a poor outcome. Its pathogenesis has to be further characterized to develop appropriate targeted therapy.